Making citizens in South East Europe through citizenship and human rights education: the results of the CIVITAS BiH regional pilot-study - Spajić-Vrkaš, Vedrana (2012)
The presentation focused on the results of a pilot-study on the outcomes of citizenship education in secondary schools conducted in 2009 in seven countries of the South East Europe, including Albania. The study was co-ordinated by CIVITAS BiH with a view to describe the assets and obstacles to teaching citizenship education in the region.